Analysis of Intrinsic and Extrinsic Coagulation Pathway Factors in OCP Treated PCOS Women - Manzoor, Saika; Ganie, Mohd A.; Majid, Sabhiya; Shabir, Iram; Kawa, Iram A.; Fatima, Qudsia; Jeelani, Humira; Yousuf, Syed Douhath; Rashid, Fouzia (Indian journal of clinical biochemistry, 2021)
Human polycystic ovary syndrome (PCOS)—a cluster of diseases displays various symptoms associated with endocrine and gynecological disorders in childbearing women. Oral contraceptive pills (OCP) being a drug of choice minimizes symptoms and complications associated with the disorder. But, the controversial data available in literature regarding use of OCPs compels us to setup a study design regarding effect of OCP treatment in PCOS subjects and the possible outcomes specifically regarding coagulation pathways. Two PCOS study groups have been selected according to Rotterdam Criteria: one with OCP treatment (n = 50) and other without any drug treatment i.e., drug naive (n = 50). Anthropometry, Biochemistry, Hormones, Insulin and various clotting factors like Factor XI, Factor V, tPA, TAT-III and D-dimer were analyzed in both groups. The results showed worsening of IR, Metabolic parameters and coagulopathy in OCP group comparative to drug naive group indicating adverse effects of the OCP treatment which puts these women at risk for number of future clinical implications especially Cardiovascular and metabolic complications.